Stars, Self, Control: A Comparative Study on Astrological Beliefs, Personality Traits and Locus of Control Among Millennials and Centennials - Arthika S.; Kavisha S.K.; Hrishikesh Basumatary; Dr. G. Sajeeth Kumar (International Journal of Indian Psychȯlogy, 2025)
The present study compared astrological belief, personality traits, and locus of control between Millennials and Centennials. Astrological belief has resurged recently, especially among younger people, influenced by digital platforms and social media. This research investigated how different generations vary in their beliefs about astrology, Big Five personality traits, and locus of control, aiming to understand the influence of cultural and technological evolution on psychological concepts. A comparative cross-sectional approach was employed, involving 108 participants where 54 Millennials and 54 Centennials were chosen through stratified random sampling. Information was gathered using the Belief in Astrology Inventory, the short form of the Big Five Inventory-2, and the Locus of Control Scale. Independent t-tests were used to assess differences between generations and across genders. The findings revealed that among the two generations, millennials scored higher in astrological belief, while centennials scored higher in openness and locus of control. No significant differences were observed in personality traits between the two groups. In the context of genders, no significant difference was found in astrological belief and locus of control, but women scored higher in the traits like conscientiousness and agreeableness.